The professional field of Social and Solidarity Economy Technicians from Universidad Nacional de Quilmes, Argentina - Zeballos, Tania Ludmila; Mendy, Guillermina; Altschuler, Bárbara (Cooperativismo & Desarrollo, 2021)
This document proposes an approach to the characterization of the professional field of the University Technicians [Associate Degrees] in Social and Solidarity Economy of the National University of Quilmes (unq), Buenos Aires, Argentina, by means of a survey of their practices and socio-labor activities. The University Degree in Social and Solidarity Economy (tuess in Spanish) is an innovative educational path and a foundatio-nal space in institutionalizing training processes in Social and Solidarity Economy (sse) in our country, where multiple pedagogical devices that facilitate collective and inclusive teaching and learning processes. tuessbegan in 2012 and is part of the Southern Observatory of Social and Solidarity Economy (CREES) an Academic Unit of the Department of Economics and Administration of the unq. On a universe of 261 graduates to date, through a methodological triangulation we conducted surveys (surveys and interviews), systematizations and analysis of some variables on the graduates of the 2014-2019 periods, identifying their professional practices from the characteristics that this path offers and recognizing practices that re-signify and re-construct sub-jectivities, values, and knowledge. This work is framed within the line of research on Education and Social and Solidarity Economy that we have been developing since 2012 at the unq, currently developed from the project “University, markets and public policies in Social and Solidarity Economy” (of the “Scopes and Challenges of Territorial Development” Program), as well as from a Research Initiation Scholarship from the Research Secretariat of the unq. The document gives an account on the innovative characteristics of this training course in sse, its pedagogical and didactic proposal, providing an initial analysis of this emerging professional field and its configuration in our country.